Extraspinal ossifications after implantation of vertical expandable prosthetic titanium ribs (VEPTRs) - Zivkovic, Vanja (Springer Berlin Heidelberg, 2014)
INTRODUCTION: Though developed for thoracic insufficiency syndrome, the spinal growth-stimulating potential and the ease of placement of vertical expandable titanium ribs (VEPTRs) has resulted in their widespread use for early-onset spine deformity. Observation of implant-related ossifications warrants further assessment, since they may be detrimental to the function-preserving non-fusion strategy. PATIENTS AND METHODS: Radiographs (obtained pre and post index procedure, and at 4-year follow-up) and the records of 65 VEPTR patients from four paediatric spine centres were analysed. Ossifications were classified as type I (at anchor points), type II (along the central part) or type III (re-ossification after thoracostomy). RESULTS: The average age at the index procedure was 6.5 years (min 1, max 13.7). The most prevalent spine problem was congenital scoliosis (37) with rib fusions (34), followed by neuromuscular and syndromic deformities (13 and 8, respectively). Idiopathic and secondary scoliosis (e.g. after thoracotomy) were less frequent (3 and 4, respectively). Forty-two of the 65 (65 %) patients showed ossifications, half of which were around the anchors. Forty-five percent (15/33) without pre-existing rib fusions developed a type II ossification along the implant. Re-ossifications of thoracostomies were less frequent (5/34, 15 %). The occurrence of ossifications was not associated with patient-specific factors. CONCLUSIONS: Implant-related ossifications around VEPTR are common. In contrast to harmless bone formation around anchors, ossifications around the telescopic part and the rod section are troublesome in view of their possible negative impact on chest cage compliance and spinal mobility. This potential side effect needs to be considered during implant selection, particularly in patients with originally normal thoracic and spinal anatomy.